Simulation of a Queuing System of a Post Office in Anylogic Software - Silvia Dutkova; Karol Achimsky; Pawel Drozdziel (Communications - Scientific letters of the University of Zilina, 2020)
This paper displays the design and application of a model that simulates the queuing system of a fictional post office. Starting point for solving more complicated optimization tasks is to create a system model that consists of elements of reality and the relationships between these elements. The key part of the paper includes the model of a queuing system of a post office created in Anylogic simulation software. The model of the post office displays post office with 5 postal counters, a certain input flow and a certain service time with an exponential probability distribution. The model also includes statistics and cost calculation.